From mind to text : continutities and breaks between cognitive, aesthetic and textualist approaches to literature - Stopel, Bartosz (Routledge interdisciplinary perspectives on literature ;, 2018)
From Mind to Text: Continuities and Breaks Between Cognitive, Aesthetic and Textualist Approaches to Literature explores the historical context of theory formation and of its contemporary status, including an overview of debates about theory's role in literary studies provided both by representatives of theory itself, as well as by those who distance themselves from it.